An Initial Look at Contracted Wildfire Response Capacity in the American West. Issue 1 (3rd December 2018) - Huber-Stearns, Heidi; Moseley, Cassandra; Bone, Christopher; Mosurinjohn, Nathan; Lyon, Katie M
Abstract: As the need for fire suppression has grown, private contractors have become increasingly important in providing equipment and services to support agency wildfire suppression. Understanding the capacity and regional variation of contracted resources for federal agency fire suppression needs across the western United States is critical for efficient and effective fire planning and response. Using initial 2015 preseason agreement data for wildfire equipment and services from the Virtual Incident Procurement system, we examined how equipment amount and diversity vary considerably across the western United States. Equipment and services particularly concentrated in the Northwest and Northern California Geographic Areas.